Transcriptomic Landscape and Functional Characterization of Human Induced Pluripotent Stem Cell-Derived Limbal Epithelial Progenitor Cells - Polisetti, Naresh; Rapp, Julian; Liang, Paula; Dettmer-Monaco, Viviane; Bucher, Felicitas; Pruszak, Jan; Schlötzer-Schrehardt, Ursula; Cathomen, Toni; Schlunck, Günther; Reinhard, Thomas (Cells, 2022)
Limbal stem cell deficiency (LSCD) is a complex, multifactorial disease affecting limbal epithelial progenitor cells (LEPC), which are essential for maintaining corneal stability and transparency. Human induced pluripotent stem cell-derived (hiPSC-) LEPC are a promising cell source for the treatment of LSCD. However, their similarity to native tissue-derived (T-) LEPC and their functional characterization has not been studied in detail. Here, we show that hiPSC-LEPC and T-LEPC have rather similar gene expression patterns, colony-forming ability, wound-healing capacity, and melanosome uptake. In addition, hiPSC-LEPC exhibited lower immunogenicity and reduced the proliferation of peripheral blood mononuclear cells compared with T-LEPC. Similarly, the hiPSC-LEPC secretome reduced the proliferation of vascular endothelial cells more than the T-LEPC secretome. Moreover, hiPSC-LEPC successfully repopulated decellularized human corneolimbal (DHC/L) scaffolds with multilayered epithelium, while basal deposition of fibrillary material was observed. These findings suggest that hiPSC-LEPC exhibited functional properties close to native LEPC and that hiPSC-LEPC-DHC/L scaffolds might be feasible for transplantation in patients suffering from LSCD in the future. Although hiPSC-LEPC-based stem cell therapy is promising, the current study also revealed new challenges, such as abnormal extracellular matrix deposition, that need to be overcome before hiPSC-LEPC-based stem cell therapies are viable.
CRIS-Team Scopus Importer:2022-12-23
Keywords: anigogenesis; corneal tissue engineering; decellularized limbal scaffolds; immuneresponse; induced pluripotent stem cells; limbal epithelial progenitor cells; limbal niche cells; limbal stem cells; melanocytes; RNA-sequencing